Characterization and Evaluation of the Recovery Process of Saturated Reverse Osmosis Membranes by Chemical Oxidation - Romero-Figueroa, J (Elsevier B.V., 2025)
The increasing adoption of membrane technologies in desalination has led to a substantial accumulation of end-of-life reverse osmosis membranes. Disposal becomes necessary when the saturation of the polyamide active layer reduces the membrane permeate fluxes to a level where recovery through chemical washing is not feasible. Membrane recycling techniques via chemical modification can offer an alternative to provide membranes with a second use and prolong the material s lifespan. The present work evaluates the oxidation process of saturated reverse osmosis membranes used in brackish water treatment. The concentration and the exposure time of the oxidizing agent were analyzed and assessed through filtration tests in a stirred cell. Membranes underwent chemical, topological and operational analyses for characterization. The results indicate a consistent increase in water permeability ranging from 151 % to 1342 % with higher exposition to the oxidizing agent. In the case of the membrane with the highest exposure (3.0 % NaOCl for 180 min), a permeability of 31.4 ± 5.3 L m−2 h−1 bar−1 and a NaCl rejection of 15.1 ± 0.2 % were achieved. Surface characterization tests revealed partial degradation of the polyamide layer, showcasing separation properties similar to commercial nanofiltration membranes. The resulting membranes were tested for application in groundwater and greywater treatment. This research demonstrates the feasibility of modulating the degree of oxidation based on the desired application for the recycled membranes. © 2024 Elsevier B.V.